The School Readiness Analysis in 2021/2022 Academic Year Amid Covid-19 Pandemic Based on The Regional Economic Resilience in Salatiga - Sri Sulandjari (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
The Covid-19 pandemic is devastating people’s general income. It also affects the education sector. The government attempted to create an infrastructure as a solution to reduce the pandemic's impact. Economic resilience is a factor that shows the economic resources resilience in the midst of problems. Therefore, to understand the readiness level of people in Salatiga when welcoming the ‘new normal’ from WFH-online to offline activities, we use the economic resilience factors as indicators. Based on the research, it was found that Salatiga is gradually improving oneself to make the ‘new normal’ agenda succeed. This happens because Salatiga economic has decreased yet still afford for recovery.